An Unconventional Splitting for Korteweg de Vries-Burgers Equation (European Journal of Pure and Applied Mathematics, 2015)
Numerical solutions of the Korteweg de Vries--Burgers (KdVB) equation based on splitting is studied. We put a real parameter intoÂ a KdVB equation and split the equation into two parts. The real parameter that is inserted into the KdVB equation enables us to play with the splitted parts. The real parameter enables to write the each splitted equation Â as close to the Korteweg de Vries (KdV) equation as we wish and as far from the Burgers equation as we wish or vice a versa. Then we solve the splitted parts numerically and compose the solutions to obtained the integrator for the KdVB equation. Finally we present some numerical experiments for the solution of the KdV, Burger's and KdVB equations. The numerical experiments shows that the new splitting gives feasible and valid results.Â